Some Candles Emit Materials Hazardous for Human Health and are Indoor Air Pollutants - Massoudi , Ruhullah; Hamidi , Amid (Current Innovations in Disease and Health Research Vol. 1, 2023)
The purpose of this research was to carefully study the kind of chemicals produced by burning paraffin-based candles and compare the results by burning candles made from another source specifically from soybean. This research work is carried out in order to prove that burning paraffin candles in enclosed environment would be enormously dangerous, then it would be absolutely necessary to avoid it. Various chemicals produced by burning candles under normal condition were identified using a Perkin-Elmer TurboMass GC/MS system equipped with a NIST Library of compounds; also Shimadzu GC-2010 gas chromatograph and QP-2010s quadruple mass spectrometer. The chromatograms of emission products of various candles were tested for hazardous emissions. Variety of hazardous materials were produced from burning paraffin candles among those were benzene and toluene all of which are quite dangerous for human health. The EPA has classified benzene as known human carcinogen for all routes of exposure. The principal effect of toluene exposure is central nervous system depression. Petroleum-based candles produced various alkanes, alkenes, alcohols, benzene, toluene, naphthalene, and some other chemicals, while soybean-based candles were seemingly clean that produced no observable peaks. Apparently, burning petroleum based candled produce unwanted materials some of which are pollutants and would be hazardous to inhale for a longer period of time.